Promoting deep learning through a concept map-building collaborative activity in an introductory programming course - Barros, João Paulo (2024)
Programming courses focus heavily on problem-solving and coding practice. However, students also face numerous interrelated concepts that should be given more attention to foster more effective and comprehensive learning. Often, students only get an incomplete knowledge of those concepts and their relations as no adequate reflection is promoted or even seen as necessary. The result is a superficial surface learning about essential programming concepts and their relations. This experience report presents a learning activity to promote deep learning of concepts and their relations. The activity challenges students to specify relations between concepts. Students search definitions for a given set of concepts and define relations between those concepts in textual form. To that end, they use a freely available tool that produces a graph from textual descriptions. This tool dramatically simplifies and speeds up the creation of readable graphical representations. Although many different courses can take advantage of the presented activity, we present the activity’s application to an introductory object-oriented programming course. We also present and discuss the student’s feedback, which was highly positive. In the end, we provide recommendations, including possible variations. These can help educators to effectively foster active learning of concepts and their relations in their classrooms.